A botanist's guide to society and secrets - Khavari, Kate (Khavari, Kate. Saffron Everleigh mystery, 2024)
London, 1923. Returning from Paris, botanical researcher Saffron Everleigh finds that her former love interest Alexander Ashton’s brother, Adrian, is being investigated for murder. A Russian scientist working for the English government has been poisoned, and expired in Adrian’s train compartment. Alexander asks Saffron to put in a good word for Adrian with Inspector Green. Despite her unresolved feelings for Alexander, Saffron begins to unravel mysteries surrounding the dead scientist.